IBNU THUFAIL SEBAGAI MODEL PERADABAN ISLAM - Ahmad Zaki Mubarak (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
This paper studies one of the ntayor of muslinr philosophy tlrat's lbn Thulail, known as Abu Bacer in Latin t-anguagc. According to thc writcr, the illurnination thought of Ibn Thul-ail lourrd on the story of' I-layy iltn Yuq:hun at lcast also an exantple ot- knowlcdge thcory. l-hc illuntinalion thoght ol'lbnLr T'hufail was his combination and interection with thc philosophy tradtion in that timc, tlrat tlrc plrilosophical tlrougltt of'Aviccnna. So, it's unclcrstaltd fiorn thc statement of Ibnu T'hu{ail lris sclf that his illunrination thouglrt lound ilr thc story of Ilqtlt illp Yaqzhan is thc explanation ol thc sccrcct of oticntcl plr i losolllry ol' Av iccttttc.